A SURVEY ON LABOR MARKETS IMPERFECTIONS IN MEXICO USING A STOCHASTIC FRONTIER - VILLA, Juan M. (Theoretical and Practical Research in Economic Fields; Vol 1 No 1 (2010): TPREF, Volume I, Issue 1(1), Summer 2010, 2010)
It is assumed that observed labor income is the result of three stages across the job search process from the reservation wage formation, the bargaining between employers and potential employees when the match, and finally a possible additional adjustment once the worker is completely hired. This paper provides a methodological proposal and an intuitive estimation of the wage gain due to the presence of labor market imperfections across those three stages. The part of the wage that is explained by labor markets imperfections is estimated by performing a stochastic frontier model with panel data belonging to the Mexican labor survey – ENOE. The results suggest that 82.7% of the variance of the wages of the subordinated workers is explained by market imperfections. Moreover, public labor offices and small firms are negatively correlated with their presence.